Neutrinos from captured dark matter in galactic stars - Debajit Bose; Rohan Pramanick; Tirtha Sankar Ray (Physics Letters B)
Sub-GeV neutrinos produced in a stellar core may emerge from main sequence stars, white dwarfs and brown dwarfs producing possible observable signals of dark matter capture. A distribution of these stars near the Milky Way galactic center will produce a neutrino flux that can be probed at Earth based neutrino observatories like Super-Kamiokande and Hyper-Kamiokande. We demonstrate that this can provide a handle to probe dark matter masses in the 200MeV−2GeV mass scales that compares favourably with present day direct detection bounds.